Temperature, osmolality, and glucose determine the erythrocyte resistance to post-hypertonic stress - Semionova, K.A.; Nipot, O.E; Yershova, N.A.; Shapkina, O.О.; Shpakova, N.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The effect of glucose on the sensitivity of human and rabbit erythrocytes to post-hypertonic shock has been investigated. The level of post-hypertonic hemolysis of human and rabbit erythrocytes was found to depend on the dehydration medium and to increase with a rise in the salt concentration in it. An analysis of the sensitivity of these cells to the effects of post-hypertonic shock showed that rabbit erythrocytes were more resistant, i.e. at 37 °C, the injury rate of rabbit erythrocytes was at least a half lower of that for human cells; at 0 °C, the effect was less pronounced. The level of post-hypertonic hemolysis of the erythrocytes pretreated with glucose was determined by endogenous (species belonging to erythrocytes) and exogenous factors (modifier concentration and post-hypertonic shock conditions). In case of human erythrocytes, glucose was capable of reducing the post-hypertonic hemolysis, which exceeded 50 %. If, under conditions of post-hypertonic shock, glucose in a high concentration (5 %) was effective at 37 and 0 °C, then, in low (0.6 %) one, it was effective only at 0 °C. In rabbit erythrocytes, glucose was capable of reducing a post-hypertonic hemolysis only when used at a high concentration (5 %) in post-hypertonic shock at 37 °C. Glucose is thought to form hydrogen bonds with cytoplasmic proteins, which impedes the binding of sodium ions to them. This prevents the excess flow of ions into a cell during the dehydration step and, accordingly, the development of erythrocyte injury during rehydration. It is envisaged that the adherence to near-zero temperatures when thawing human erythrocytes and removing cryoprotectants will allow the use of lower concentrations of glucose to achieve a protective effect and prevent its toxic effect on cells.